Ударное взаимодействие тел при наличии порошкового слоя - Анциферов, А. В. (НТУ "ХПИ", 2009)
Досліджується віброударна система, що моделює процес руйнування шару матеріалу у вертикальному вібраційному млині. У теоретичній частині роботи пропонується використовувати методитеорії пружності для вирішення контактних задач. Проведено експеримент за визначенням радіусу плями контакту, що формується кулею при ударі по площині через шар порошку.

The research of the vibroimpact system, modeling the process of material layer destruction in a vertical vibration mill, is conducted. In theoretical part of work it is suggested to utillize the methods of theory of resiliency for the decision of contact tasks. An experiment is conducted on determination contact radius of spot, formed a ball at a blow to the plane through the layer of powder.
Keywords: помольная камера; измельчение; виброударные системы; виброкипящий слой; объем деформирования; теория упругости; теория удара